Breakdown of Far-Field Raman Selection Rules by Light-Plasmon Coupling Demonstrated by Tip-Enhanced Raman Scattering - Poliani, Emanuele; Wagner, Markus R.; Vierck, Asmus; Herziger, Felix; Nenstiel, Christian; Gannott, Florentina; Schweiger, Manuel; Fritze, Stephanie; Dadgar, Armin; Zaumsei, Jana; Krost, Alois; Hoffmann, Axel; et al. (Journal of Physical Chemistry Letters, 2017)
We present an experimental study on the near-field light-matter interaction by tip-enhanced Raman scattering (TERS) with polarized light in three different materials: germanium-doped gallium nitride (GaN), graphene, and carbon nanotubes. We investigate the dependence of the TERS signal on the incoming light polarization and on the sample carrier concentration, as well as the Raman selection rules in the near-field. We explain the experimental data with a tentative quantum mechanical interpretation, which takes into account the role of plasmon polaritons, and the associated evanescent field. The driving force for the breakdown of the classical Raman selection rules in TERS is caused by photon tunneling through the perturbation of the evanescent field, with the consequent polariton annihilation. Predictions based on this quantum mechanical approach are in good agreement with the experimental data, which are shown to be independent of incoming light polarization, leading to new Raman selection rules for TERS.
CRIS-Team Scopus Importer:2022-04-14